JOB INSECURITY DAN WORK ENGAGEMENT DOSEN DALAM MENJALANKAN INNOVATIVE WORK BEHAVIOR - Barkhowa, Mokhammad Khukaim Barkhowa (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
The task of lecturers is to transform, develop, and disseminate technology, science through teaching, research, and community service. Thus, all tasks and responsibilities become the workload of lecturers. To make higher education in Salatiga City a success and also to accelerate the realization of the welfare of the people of Salatiga City, it is necessary to increase innovative work behavior so that lecturers can realize new ideas. The problem to be studied is how job insecurity and work engagement affect innovative work behavior in lecturers in Salatiga City. The purpose of this study is to examine how job insecurity and work engagement affect innovative work behavior in lecturers in Salatiga City. This scientific study was conducted by lecturers in Salatiga City based on the Central Statistics Agency of Salatiga City, totaling 1,079 lecturers. Due to limitations, sampling was carried out in this study using calculations with the Slovin formula with a sample size of 92 lecturers. Sampling used simple random sampling. The data analysis tool to answer the research hypothesis used multiple regression analysis. The results of the study showed that job insecurity had a negative and significant effect on innovative work behavior and work engagement had a positive and significant effect on innovative work behavior. Suggestions for lecturers and universities in Salatiga City are that lecturers do not feel that there are threats that occur and affect their work in the current digital era and that lecturers are willing to work overtime to complete their work.